Outside Cover Picture: Plasma Process. Polym. 4/2020. Issue 4 (3rd April 2020) - Chang, Zhengshi; Wang, Cong; Zhang, Guanjun
Abstract : Outside Front Cover : Plasma technology has shown the important role in environment protection field and relative disciplines. We reviewed here the research progress of VOC degradation related to the plasma technology which benefits from the retrievable excellent researches. The degradation mechanism of VOCs when the plasma was introduced in reactions was discussed from different views. They are plasma alone, and plasma cooperating with the other technologies, such as catalyst, adsorbent, biotreatment, etc. Further details can be found in the article by Zhengshi Chang, Cong Wang, and Guanjun Zhang (e1900131 ).